Children’s Nutrition Status Based on Streetism, Mobility, and Social Cohesion Perspective in Makassar (Study Epidemiology Analytic) - Samsualam1 , Masriadi 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. Changes in community structure from argument to industry and lifestyle changes, socio economic societies are suspected as a backdrop to the increasing prevalence of non-communicable diseases, so that the incidence of non-communicable diseases varies greatly in epidemiological transitions. One of the epidemiological problems that often arises is the problem of child nutrition. Street children nutrition is very concern in Makassar City. Street children in Makassar city are increasing every year. This was seen in 2014 the number of street children was 220, in 2015 there were 250 children, while in 2016 it increased to 305 street children. Street children are at risk of suffering from nutritional disorders. The nutritional status of street children is very dependent on mobility, streetism, mobility, and social cohesion. The study was conducted with the aim of analyzing the nutritional status of street children based on the perspective of streetism, mobility and social cohesion in Makassar. The benefits of this research are expected to be able to develop theories and concepts regarding the nutritional status of street children based on epidemiological studies. Material and Methods The type of research used was an observational method in a cross-sectional study design. The sampling method uses simple random sampling. The study was conducted in September January 2020. The number of sampling was 90 people. The population and research sample are street children in Makassar City. The data analysis technique used in this study is Chi-square. Results. There is an influence of streetism and social cohesion on street children in Makassar. The results of the analysis of the relationship between streetism, mobility and social cohesion with the nutritional status of street children found that streetism p (0,000) <p (0.05), mobilitas p (0,075) p > (0,05), kohesi social p (0,075) p > (0,05). Conclusion. Streetism has a very significant influence on the status of street children in Makassar. It is recommended that the social service and health office work together with halfway houses to provide information on nutrition to street children so that they understand about nutritious food, healthy eating patterns.